Secondary Data Analysis: Comparison of ESBL- and Carbapenemase-Producing Bacterial Resistance from Pneumonia Patient Sputum Samples - Husjain Djajaningrat; Atiek Kusumah; Angki Purwanti; Diah Lestari; Tri Prasetyorini (Jurnal Kesehatan Cendikia Jenius, 2025)
Antibiotic resistance mediated by Extended-Spectrum Beta-Lactamase (ESBL) and Carbapenemase-producing bacteria represents a serious challenge in the management of pneumonia. This study aimed to compare the resistance patterns of ESBL- and Carbapenemase-producing bacteria isolated from sputum samples of pneumonia patients in specialized and non-specialized care units at Bekasi Hospital. A comparative descriptive study with a cross-sectional approach was conducted using secondary data from sputum culture and antibiotic susceptibility testing collected between 2015 and 2024. A total of 116 bacterial isolates were included through total sampling, consisting of 58 isolates from specialized units and 58 from non-specialized units. Data were analyzed using univariate analysis and bivariate analysis with the Chi-square test. The results showed that ESBL-producing Klebsiella pneumoniae was the most predominant isolate (39.7%) and was evenly distributed between both care settings. The highest resistance was observed against beta-lactam and cephalosporin antibiotics, while Meropenem and Amikacin remained highly effective against ESBL-producing bacteria. No significant difference was found in the distribution of ESBL and Carbapenemase-producing bacteria between specialized and non-specialized units (p = 0.707). In conclusion, the widespread presence of resistant bacteria across all care units highlights the need to strengthen resistance surveillance, implement comprehensive antibiotic stewardship programs, and enforce strict infection prevention and control measures throughout hospital settings.